The interface of history and fiction in Russel Brownlee's Garden of the plagues, Ingrid Winterbach's To hell With Cronjé, and Etienne van Heerden's The long silence of Mario Salviati - Wyrill, Beth Alexandra (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2014)
Both historiographical and literary practices have undergone revision in recent years in attempting to address the inheritance of nineteenth-century realism. Since the object of realist stylistics, employed in both the writing of fiction and history, is to render authorship authoritative or even invisible, the ideological import of these narratives is often such that the constructedness of the historical record and its absences are veiled. In developments beginning in the 1980s with the advent of 'New Historicism' and with the emergence of postmodern literary techniques, the interface of literature and history became of seminal importance, since both were now credited as being products of narrative and discourse, and hence, to varying degrees, of the literary imagination. This movement intersects interestingly with developments in postcolonial studies, since it is the voices of the marginalized and disempowered colonized peoples that are routinely co-opted and excised from nineteenth-century realist histories. These concerns are now being fully explored in the literature of the contemporary post-transitional South African moment, since authors in this country seemingly now feel freed up to look back to histories that precede the immediate traumas of apartheid. The concern, in relation to apartheid developments but also on a broader universal scale, is this: if history is viewed as perpetual emergences of modernities, then one of the great absences in the record is the historical determinants of any given epistemology. The attempt to recreate such an epistemological genealogy is thus simultaneously postcolonial, historiographical, and literary. Russel Brownlee's Garden of the Plagues (2005), Ingrid Winterbach's To Hell with Cronjé (2010), and Etienne van Heerden's The Long Silence of Mario Salviati (2002) attempt to bridge this gap in the recorded sensibilities of any historical moment by representing a 'lived experience' of the past, and in the process imaginatively recreating the cultural, historical and psychological locations of the proponents of an emerging modernity. This study concerns itself with the ways in which these authors address the influence of realist historiography through the use of literary innovations that allow for the departure from realist stylistics. Most commonly, all three authors draw on forms of magic realism, but multiple refigurings and recombinations of notions of temporality, narrative, and characterization likewise work to defamiliarize the once stable discourse of history.
Keywords: Brownlee, Russel -- Criticism and interpretation; Winterbach, Ingrid -- Criticism and interpretation; Van Heerden, Etienne, 1954- -- Criticism and interpretation; South African fiction (English) -- History and criticism; South African fiction (English) -- 20th century -- History and criticism; African fiction (English) -- 21st century -- History and criticism; Brownlee, Russel -- Garden of the plagues; Winterbach, Ingrid -- Niggie -- English; Van Heerden, Etienne, 1954- -- Swye van Mario Salviati -- English; Historical fiction -- History and criticism; Magic realism (Literature)